Jaw‐Muscle Fiber Architecture and Leverage in the Hard‐Object Feeding Sooty Mangabey are not Structured to Facilitate Relatively Large Bite Forces Compared to Other Papionins. Issue 2 (13th January 2018) - Taylor, Andrea B.; Terhune, Claire E.; Toler, Maxx; Holmes, Megan; Ross, Callum F.; Vinyard, Christopher J.
ABSTRACT: Numerous studies have sought to link craniofacial morphology with behavioral ecology in primates. Extant hard‐object feeders have been of particular interest because of their potential to inform our understanding about the diets of early fossil hominins. Sooty mangabeys ( Cercocebus atys ) are hard‐object feeders that frequently generate what have been described as audibly powerful bites at wide jaw gapes to process materially stiff and hard seeds. We address the hypothesis that sooty mangabeys have features of the masticatory apparatus that facilitate this feeding behavior by comparing fiber architecture and leverage of the masseter and temporalis muscles between sooty mangabeys and three papionin primates that do not specialize on hard objects. Contrary to predictions, sooty mangabeys do not have relatively larger muscle physiologic cross‐sectional areas or weights compared to other papionins, nor do they consistently display improved leverage. In this regard, sooty mangabeys differ in their morphology from other hard‐object feeders such as tufted capuchins. However, males of all four papionin species converge on a shared pattern of relatively longer anterior superficial masseter fibers compared with female conspecifics, suggesting that males are likely prioritizing muscle stretch to improve gape performance as part of a behavioral repertoire that includes agonistic social interactions and intense male–male competition. These findings strengthen support for the hypothesis that gape display behaviors can exert a strong selective influence throughout the musculoskeletal masticatory apparatus. Results also raise questions about the morphological suitability of extant cercopithecines as models for interpreting feeding behavior and diet in fossil hominins with limited jaw gape capacity. Anat Rec, 301:325–342, 2018. © 2018 Wiley Periodicals, Inc.